Proposed learning modules on mathematics for grade six fast learners - Abille, Lydia Sotelo 1939-; Baldo, Trinidad C. (Quezon City College of Education, University of the Philippines Diliman 1976.)
The study proposed a method of approach in the teaching of Mathematics to Grade Six fast learners which involves the learner in an educative process which will ensure his maximum fulfillment and self-realization as a member of society. The twenty-four learning modules proposed in the study are based on Grade Six Elementary Mathematics. These modules are patterned after the learning modules of Arends, Masla, and Weber. Certain adaptations, however, were made to suit the needs and abilities of Grade Six fast learners who are the prospective users of these learning modules.
Vita.
Thesis (Master of Arts in Teaching Special Education - Giftedness)--University of the Philippines, Diliman
Keywords: Mathematics -- Study and teaching (Elementary) -- Philippines -- Olongapo City (Zambales); Gifted children -- Education (Elementary) -- Philippines -- Olongapo City (Zambales); Teaching -- Philippines -- Olongapo City (Zambales) -- Aids and devices